Potential application areas and benefits of blockchain-enabled smart contracts adoption in infrastructure Public-private partnership (PPP) projects - Emmanuel Chidiebere Eze; Ernest Effah Ameyaw (Sustainable Futures)
The traditional, paper-centric infrastructure public-private partnership (PPP) contracts have experienced record numbers of failures and terminations due to contract compliance issues, lack of trust and transparency, and information distortions. While studies on the adoption of blockchain and smart contracts in PPP are still growing, a quantitative survey of global experts on the application areas and potential benefits of Blockchain-enabled smart contracts (BSC) in the context of PPP is lacking. This study comprehensively examined the potential application areas and benefits of BSC adoption in infrastructure PPP projects to understand their impact on the decision to digitalise PPP and ensure sustainable PPP project performance. The snowball sampling technique and questionnaire were used to gather data from experts across countries. Data analysis was done using means analysis, normalisation value, coefficient of variation, Kendall's coefficient of concordance, Kruskal-Wallis test and partial least square-structural equation modelling (PLS-SEM). The study found high awareness and knowledge of the potential benefits of smart contract adoption in infrastructure PPP projects. The leading benefits of BSC adoption in PPP are (1) decentralisation of payments and other transactions, (2) enhancing supply chain visibility and integration, (3) the autonomy in contract administration, (4) prevent misapplication of contractual provisions, and (5) enhances alternative dispute resolution (ADR). The PLS-SEM revealed that six of the eight hypothetical paths were significant. This study advocated for promoting the digitalisation of infrastructure PPP projects. It could serve as an essential resource to policymakers and industry professionals in their quest to improve PPP project performance and minimise failures.